2017
DOI: 10.1016/j.celrep.2017.08.029
|View full text |Cite
|
Sign up to set email alerts
|

A Fatty Acid Oxidation-Dependent Metabolic Shift Regulates Adult Neural Stem Cell Activity

Abstract: SummaryHippocampal neurogenesis is important for certain forms of cognition, and failing neurogenesis has been implicated in neuropsychiatric diseases. The neurogenic capacity of hippocampal neural stem/progenitor cells (NSPCs) depends on a balance between quiescent and proliferative states. Here, we show that the rate of fatty acid oxidation (FAO) regulates the activity of NSPCs. Quiescent NSPCs show high levels of carnitine palmitoyltransferase 1a (Cpt1a)-dependent FAO, which is downregulated in proliferatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
261
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(285 citation statements)
references
References 65 publications
(98 reference statements)
17
261
0
3
Order By: Relevance
“…As a proof of this notion, perturbation of mitochondrial function in quiescent radial glia‐like neural stem cells due to depletion of mitochondrial transcription factor A (Tfam) reproduces multiple hallmarks of aging in hippocampal neurogenesis . In addition, other evidences elucidated the metabolic changes between quiescent and proliferative NSCs , or in the transition from NSCs to NPCs . To date only few reports have addressed the role of mitochondria during the maturation process from neuroblasts to neurons , thus a detailed metabolic characterization of this transition is still incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…As a proof of this notion, perturbation of mitochondrial function in quiescent radial glia‐like neural stem cells due to depletion of mitochondrial transcription factor A (Tfam) reproduces multiple hallmarks of aging in hippocampal neurogenesis . In addition, other evidences elucidated the metabolic changes between quiescent and proliferative NSCs , or in the transition from NSCs to NPCs . To date only few reports have addressed the role of mitochondria during the maturation process from neuroblasts to neurons , thus a detailed metabolic characterization of this transition is still incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes and NPCs are the main cell types in the brain that utilize FAO for their energy expenditure (Edmond, Robbins, Bergstrom, Cole, & de Vellis, 1987;Knobloch et al, 2017) and FAs have been shown to be produced endogenously in neuronal stem cells (Knobloch et al, 2013). This prompted us to focus this study on astrocytes and NPCs.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely supposed that brain did not use fatty acids as energy substrates (Panov et al, 2014;Schönfeld and Reiser, 2013). However, although this is true for neurons, the carnitine palmitoyl transferase (CPT) system, which allows the entry of long-chain fatty acids into the mitochondria for ß-oxidation, is functional in astrocytes (Jernberg et al, 2017;Panov et al, 2014) and in embryonic (Xie et al, 2016) and adult (Knobloch et al, 2017) neural stem cells. The role of carnitine in its anti-inflammatory or energetic functions remains to be elucidated in this model and may constitute for the future a starting point for the development of innovative therapeutic.…”
Section: Discussionmentioning
confidence: 99%